2003
DOI: 10.1046/j.1471-4159.2003.01638.x
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐induced neurite outgrowth of cerebellar granule cells is mediated by GABAA receptor activation, calcium influx and CaMKII and erk1/2 pathways

Abstract: During neuronal development, GABA A -mediated responses are depolarizing and induce an increase in the intracellular calcium concentration. Since calcium oscillations can modulate neurite outgrowth, we explored the capability of GABA to induce changes in cerebellar granule cell morphology. We find that treatment with GABA (1-1000 lM) induces an increase in the intracellular calcium concentration through the activation of GABA A receptors and voltage-gated calcium channels of the L-subtype. Perforated patch-cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 64 publications
5
59
0
Order By: Relevance
“…It seems likely that differential activation of calcium frequency-dependent effectors such as CaMKII and calcineurin would occur in each axonal process. Positive effectors such as CaMKI and CaMKII, which have been shown to promote neurite outgrowth (Borodinsky et al, 2003;Wayman et al, 2004Wayman et al, , 2006 are preferentially activated in axonal processes with higher frequencies of Ca 2ϩ transients (Tang and Kalil, 2005). CaMKII␤ has been shown to bind directly to actin filaments and increase filopodial dynamics (Fink et al, 2003), consistent with results indicating that direct elevation of Ca 2ϩ activity by photolysis of caged calcium can rapidly evoke protrusion of new filopodia through polymerization of actin filaments (Lau et al, 1999).…”
Section: Branching Of Cortical Neurons In Vitro Reflects In Vivo Bransupporting
confidence: 60%
“…It seems likely that differential activation of calcium frequency-dependent effectors such as CaMKII and calcineurin would occur in each axonal process. Positive effectors such as CaMKI and CaMKII, which have been shown to promote neurite outgrowth (Borodinsky et al, 2003;Wayman et al, 2004Wayman et al, , 2006 are preferentially activated in axonal processes with higher frequencies of Ca 2ϩ transients (Tang and Kalil, 2005). CaMKII␤ has been shown to bind directly to actin filaments and increase filopodial dynamics (Fink et al, 2003), consistent with results indicating that direct elevation of Ca 2ϩ activity by photolysis of caged calcium can rapidly evoke protrusion of new filopodia through polymerization of actin filaments (Lau et al, 1999).…”
Section: Branching Of Cortical Neurons In Vitro Reflects In Vivo Bransupporting
confidence: 60%
“…It remains that, in some experiments, we used higher doses of GABA. In accordance with previous reports (Bird and Owen, 1998;Borodinsky et al, 2003), we had to take into consideration the possibility of a rapid GABA degradation and used relatively high concentrations of GABA (100 M) for chronic treatment experiments (Ͼ5 h). Similarly, in slice cultures, high doses were required for inducing lamellipodia on a timescale similar to that of dissociated cultures.…”
Section: Discussionmentioning
confidence: 88%
“…This capping of excitability has been proposed to be critical for growth-promoting excitation without causing excitotoxicity (Ben-Ari, 2002). It has been shown that this depolarizing GABAergic input can be critical for normal neuronal development (Borodinsky et al, 2003;Ge et al, 2006), and a possible mediator of this effect could be regulated release of BDNF, the expression of which has been shown to be enhanced by GABA application (Berninger et al, 1995). Although it has been reported that depolarization-induced release of BDNF is essentially eliminated by exposure to TTX (Blochl and Thoenen, 1995;Katz, 2000, 2002;Kojima et al, 2001;Gartner and Staiger, 2002) and would therefore not be expected to occur in response to moderate sustained depolarization, it is possible that the methodology used was not sensitive enough to detect it.…”
Section: Discussionmentioning
confidence: 99%